2020
DOI: 10.1039/c9cc09145a
|View full text |Cite
|
Sign up to set email alerts
|

Stacked hexagonal prism of Ag@Ni-MOF-1 as functionalized SERS platform through rational integration of catalytic synthesis of dopamine-quinone at physiological pH with a biomimetic route

Abstract: A stacked hexagonal prism, Ag@Ni-MOF-1, was developed as an integrated SERS platform not only for in situ catalyzing in situ synthesis of DA-quinone at physiological pH, but for establishing an approach for specific determination of Cys in brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…130,183,184 For more challenging samples, such as bio-fluids which contain polymeric protein molecules that compete with the analyte for enhancing surface, the SERS substrate can be functionalized with molecular sieves to preclude the micro-sized contaminants from the enhancing surface (Figure 13A). [185][186][187] For example, Yang, et al showed that colloidal Au nanorods@metal organic frameworks (MOFs) could be used as the SERS substrate for direct detection of small molecules in whole blood. 188 In their work, a simple wet-synthesis was used to produce Au nanorods@zeolitic imidazolate frameworks-8 (Au@ZIF-8), as shown in Figure 13B.…”
Section: Size-exclusion-based Separationmentioning
confidence: 99%
“…130,183,184 For more challenging samples, such as bio-fluids which contain polymeric protein molecules that compete with the analyte for enhancing surface, the SERS substrate can be functionalized with molecular sieves to preclude the micro-sized contaminants from the enhancing surface (Figure 13A). [185][186][187] For example, Yang, et al showed that colloidal Au nanorods@metal organic frameworks (MOFs) could be used as the SERS substrate for direct detection of small molecules in whole blood. 188 In their work, a simple wet-synthesis was used to produce Au nanorods@zeolitic imidazolate frameworks-8 (Au@ZIF-8), as shown in Figure 13B.…”
Section: Size-exclusion-based Separationmentioning
confidence: 99%
“…Coupled with principal component analysis (PCA), SERS could readily distinguish Aβ 1 – 40 from Aβ 1 – 42 and differentiate their assembly stages. In addition to the normal SERS, SERS active immunosensors were designed by combining substrates with antibodies of target biomarkers to improve the sensitivity, even achieving the detection of biomarkers at fM level concentration ( Maurer et al, 2020 ; Yang et al, 2020 ). The high sensitivity of SERS may make it possible to be an effective method for early screening or diagnosis of AD.…”
Section: Raman Spectroscopic Imaging (Rsi)mentioning
confidence: 99%
“…For example, the chemical reaction between dopamine‐quinone and cysteine residues and their analogs, in which the intermediate dopamine‐quinone is unstable and difficult to occur at physiological pH in vitro. [ 51 ] Zhang and co‐workers developed Ag@Ni‐MOF‐1 substrate for catalyzing dopamine‐quinone‐cysteine reaction in vitro and for monitoring cysteine content in brain microdialysis fluid of mouse model with Alzheimer's disease (Figure 9C). [ 51a ] Ag NPs were designed as catalytic sites for dopamine oxidation and had good SERS activity.…”
Section: Application Of Mof‐sers Platformsmentioning
confidence: 99%
“…[ 51 ] Zhang and co‐workers developed Ag@Ni‐MOF‐1 substrate for catalyzing dopamine‐quinone‐cysteine reaction in vitro and for monitoring cysteine content in brain microdialysis fluid of mouse model with Alzheimer's disease (Figure 9C). [ 51a ] Ag NPs were designed as catalytic sites for dopamine oxidation and had good SERS activity. MOFs could enrich cysteine and limit it with quinones in the pore, which enabled the reaction to be completed under physiological pH in vitro (Figure 9D).…”
Section: Application Of Mof‐sers Platformsmentioning
confidence: 99%